1976
DOI: 10.1111/j.1476-5381.1976.tb07468.x
|View full text |Cite
|
Sign up to set email alerts
|

Compounds Designed to Fit a Site of Known Structure in Human Haemoglobin

Abstract: I The three-dimensional coordinates of the atoms in human haemoglobin are known, and there is a specific site in the deoxygenated form of the protein at which 2,3-diphosphoglycerate (DPG) interacts. 2 Molecular models of this site have been constructed and used to design compounds which should bind to the deoxy conformation and stabilize it. These compounds should thereby promote oxygen liberation, as does DPG. 3 The compounds so designed were found to promote oxygen liberation. Their relative potencies, as as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(72 citation statements)
references
References 30 publications
3
67
0
1
Order By: Relevance
“…Oxygen saturation curve measurements Human haemoglobin solutions of low phosphate content were prepared as described previously (Beddell et al, 1976;Paterson et al, 1976) and stored as 2 cm3 aliquots at -20°C. Saturation curve measurements on dilute haemoglobin solutions (23 tLM on a tetramer basis, 5.4 ml of solution) were carried out at 37°C in the dissociation mode using a commercially available automatic apparatus (HEMOX-ANALYZER, T.C.S.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxygen saturation curve measurements Human haemoglobin solutions of low phosphate content were prepared as described previously (Beddell et al, 1976;Paterson et al, 1976) and stored as 2 cm3 aliquots at -20°C. Saturation curve measurements on dilute haemoglobin solutions (23 tLM on a tetramer basis, 5.4 ml of solution) were carried out at 37°C in the dissociation mode using a commercially available automatic apparatus (HEMOX-ANALYZER, T.C.S.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the success in designing dialdehyde compounds to react at the 13-chain terminal amino groups (Beddell et al, 1976) and a report in the literature of certain pyridoxal derivatives reacting at either a-or P-chain terminal amino groups (Benesch et al, 1973) we turned our attention to the a-chain terminal amino region as a design site. Examination of the crystal structure data available at the time (Perutz etal., 1968;Bolton & Perutz, 1970) for horse deoxy and horse met (oxy type) haemoglobins, indicated considerable differences in structure at the a-terminal amino regions of the two forms, although the differences are not as pronounced as at the corresponding 13-terminal amino regions.…”
Section: Measurement Of Anti-sickling Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several approaches to this problem. One successful path employs interactive inspection of the structures (6)(7)(8)(9)(10). The emphasis in this paper is the complex steric features of macromolecular surfaces (11,12) at the active site of an enzyme.…”
mentioning
confidence: 99%
“…Furthermore, rational drug design (also known as structure-based drug design) through the use of computer modeling and results of x-ray diffraction is an emerging approach that is revolutionizing the practice of drug discovery. The first anti-sickling molecules designed from receptor-based molecular modeling, the substituted benzaldehyde BW12C (now referred to as 12C79), were described by Beddell et al (9). This drug has reached clinical trials, but analysis of the covalent complex of 12C79 and Hb A showed that this agent binds to the N-terminal amino group rather than the direct interaction sites of Hb S polymers including the β6Val donor site, β85Phe and β88Leu hydrophobic acceptor sites or the β4Thr-β73Asp hydrogen bond.…”
mentioning
confidence: 99%